TRIPP Is a Plant-Specific Component of the Arabidopsis TRAPPII Membrane Trafficking Complex with Important Roles in Plant Development. Issue 7 (5th May 2020) - Garcia, Veder J.; Xu, Shou-Ling; Ravikumar, Raksha; Wang, Wenfei; Elliott, Liam; Gonzalez, Efren; Fesenko, Mary; Altmann, Melina; Brunschweiger, Barbara; Falter-Braun, Pascal; Moore, Ian; Burlingame, Alma; et al.
Abstract : A proteomic study sheds light on Transport Protein Particle (TRAPP) proteins in plants and identifies TRIPP as a plant-specific component of the TRAPPII complex with important roles in vesicle trafficking and plant development. Abstract: How the membrane trafficking system spatially organizes intracellular activities and intercellular signaling networks in plants is not well understood. Transport Protein Particle (TRAPP) complexes play key roles in the selective delivery of membrane vesicles to various subcellular compartments in yeast and animals but remain to be fully characterized in plants. Here, we investigated TRAPP complexes in Arabidopsis ( Arabidopsis thaliana ) using immunoprecipitation followed by quantitative mass spectrometry analysis of AtTRS33, a conserved core component of all TRAPP complexes. We identified 14 AtTRS33-interacting proteins, including homologs of all 13 TRAPP components in mammals and a protein that has homologs only in multicellular photosynthetic organisms and is thus named TRAPP-Interacting Plant Protein (TRIPP). TRIPP specifically associates with the TRAPPII complex through binary interactions with two TRAPPII-specific subunits. TRIPP colocalized with a subset of TRS33 compartments and trans -Golgi network markers in a TRS33-dependent manner. Loss-of-function tripp mutants exhibited dwarfism, sterility, partial photomorphogenesis in the dark, reduced polarity of the auxin transporter PIN2, incomplete cross wall formation, and altered localization of a TRAPPII-specific component. Therefore, TRIPP is a plant-specific component of the TRAPPII complex with important functions in trafficking, plant growth, and development.